Uterus Transplantation as a Model for Decision Making: Islamic Perspectives - Kee Lam Wong; Waleed Fekry Faris (Yayasan Cendekia Gagayunan Indonesia, 2025)
Decision Making is an essential part of our daily living for private and public matters. These range from trivial to life-and-death situations. Man is endowed with the capacity and ability to make decisions on all earthy activities. Throughout this process, Islam demands that rationality and crucial analysis are applied before, during and after the event. In Sicknesses, intermittent or continuous decisions are often required. Apparently, the decisions are personal. However, as a patient, the recommendation or advice from the Healthcare Providers are almost mandatory for most. This is offered at the Point-of-Care. For Muslims, all advices and treatments must be lawful. Nevertheless, there could be bioethical controversies that need to be revealed and analyzed. Healthcare Providers and the patients are exposed to lots of information that may be conflicting, deceiving or irrelevant. Relying on such information may result in erroneous decisions. Healthcare Providers and Patients are in need of a common platform to direct and discuss about the most optimal options. The authors propose an Algorithmic Model, that incorporates maqāṣid shari‘ah, to simplify Decision Making at the Point-of-Care. This consists of determination of the primary medical condition(s) or issue(s), identification of key bioethical issue(s), information gathering and filtering, identification of permissibility and/or prohibitions, availability and limitation of relieves to reverse prohibitions, inputs from patient and other stakeholders leading to the recommended option. Uterus Transplantation has been advocated as treatment for Absolute Uterus Factor Infertility that is not uncommon in Muslim Countries. Through the discussion and analysis of its causes, importance of progeny, availability, permissibility and ethical considerations of various treatment options from the Islamic perspectives, this Algorithmic Model can be successfully applied at the Point-of-Care and assists patients and Healthcare Providers to make the lawful decision.